IMPROVING STUDENTS' SPEAKING SKILLS THROUGHTECHNOLOGY-MEDIATED TASK-BASED LANGUAGE TEACHING (TM-TBLT) - Ida Fauzyah, - (2023)
The emergence of significant technological advancements has resulted in changes in the student's needs, necessitating their proficiency in communication within the current digital world. This study aims to investigate how Technology-Mediated Task-Based Language Teaching (TM-TBLT) can help students to improve their speaking skills and discover their response towards it. This study was done in order to investigate the affordance the new technology in TM-TBLT, namely Generation Global website. Through this website students were able to conduct opinion exchange task and telecollaborative task. The study focuses on seven participants from eleventh grade of senior high school and employs qualitative case study design with Students' recorded audio and semi-structured interview as the instruments. The analysis of recorded audio was based on close reading, understanding, and synchronizing relaying on the theories of fluency, pronunciation, and adequacy. The analysis for semi-structured interview was through correlating interviewees' answers and the findings from the first instrument. It was found that TM-TBLT was new for students. Despite experiencing a new technique, students were able to improve their speaking skills, especially fluency and adequacy. Munculnya kemajuan teknologi yang signifikan telah mengakibatkan perubahan kebutuhan siswa, menuntut kemampuan mereka dalam berkomunikasi dalam dunia digital saat ini. Penelitian ini bertujuan untuk menyelidiki bagaimana TechnologyMediated Task-Based Language Teaching (TM-TBLT) dapat membantu siswa untuk meningkatkan keterampilan berbicara mereka dan menemukan tanggapan mereka terhadapnya. Studi ini dilakukan untuk menyelidiki kemampuan teknologi baru di TM-TBLT, yaitu situs web Generation Global. Melalui website ini siswa dapat melakukan tugas tukar pendapat dan tugas telekolaboratif. Studi ini berfokus pada tujuh peserta dari kelas sebelas SMA dan menggunakan desain studi kasus kualitatif dengan rekaman audio siswa dan wawancara semi-terstruktur sebagai instrumen. Analisis rekaman audio didasarkan pada membaca dekat, memahami, dan menyinkronkan menyampaikan pada teori kelancaran, pengucapan, dan kecukupan. Analisis untuk wawancara semi-terstruktur adalah dengan mengkorelasikan jawaban narasumber dan temuan dari instrumen pertama. Ditemukan bahwa TM-TBLT masih baru bagi siswa. Meskipun mengalami teknik baru, siswa mampu meningkatkan keterampilan berbicara mereka terutama kefasihan dan kecukupan.